Hosting multinationals: Economic and fiscal implications - Peter Egger; Marko Köthenbürger (ETH Zurich, KOF Swiss Economic Institute, 2015)
Switzerland is a prime location for both domestically owned as well as foreign-owned multinational enterprises (MNEs). In this paper, we review the literature on MNE activity with respect to its main fundamental (non-policy) drivers, the non-fiscal consequences of MNEs for various economic aggregates, and the fiscal implications associated with the operation of foreign affiliate networks. In particular, the paper puts emphasis on the fiscal implications of hosting MNEs and their relation to the current tax environment in Switzerland.
Keywords: H25; D21; F23; 330; fiscal competition; multinational firms; globalization; corporate tax avoidance